Andean Countries : A Strategy for Forestry, Volume 1. Executive Summary - FAO; World Bank (FAO, Rome, 2014)
The World Bank's revised forest policy came into being in 2002 and covers all types of forests. It has the following key objectives: (i) harnessing the potential of forests to reduce poverty in a sustainable manner; (ii) integrating forests effectively into sustainable development; and (iii) protecting vital local and global environmental services and values. The policy enables the bank to fully engage in forestry throughout the developing world, while ensuring that it complies with such safe guard policies such as OP 4.01 (Environmental Assessment), OP 4.04 (Natural Habitats) and OD 4.20 (Indigenous Peoples). On the other hand, the policy provides only a general framework for its lending operations in forestry and cannot take account of the individual socio-economic and environmental needs of regions and sub regions. To carry out the work, experienced local consultants were recruited to prepare country level reports following guidelines provided by the FAO Investment Centre, the aim being to gain a strong local perspective on the main issues and potential for sustainable and equitable growth in the sector. These reports were complimented by reference to an extensive literature base to produce individual country reports and the summary which follows. Given the complexity of forestry in the region, the need to involve large numbers of stakeholders, and the need to accommodate change, the findings of this report should not be regarded as definitive, but rather as a first step to shaping the Bank's interventions in the sector in individual countries over the medium term. It should also be noted that data have been obtained from a variety of sources, and that inconsistencies and gaps were common; they should consequently be regarded as orders of magnitude.